Transcutaneous Tibial Nerve Stimulation as Therapy for Functional Constipation - Gokce, Aylin Hande; Gokce, Feridun Suat; Iliaz, Raim; Gulaydin, Nihat (Turkish Journal of Gastroenterology, 2022)
Background: Functional constipation is a common disorder that is difficult to treat on occasion. Symptoms of this condition can per- sist despite dietary modification, exercise, and medication. Results of neuromodulation with nerve stimulation have been promising in terms of efficiency for treatment-resistant patients. This study aimed to investigate the efficacy of bilateral transcutaneous tibial nerve stimulation as a noninvasive treatment method for functional constipation. Methods: We evaluated 105 patients with functional constipation diagnosed using the Rome IV criteria. Bilateral transcutaneous elec- trical nerve stimulation was utilized for transcutaneous tibial nerve stimulation for 6 weeks; 3 sessions were conducted every week, with each session lasting for at least 30 minutes. The Constipation Severity Instrument was used before treatment, at the end of 6 weeks, and at 12 weeks (6 weeks after the end of treatment). The effects of transcutaneous tibial nerve stimulation on the time spent in the toilet and the use of softeners were investigated. Results: Of the 105 patients included in the study, 41 (39%) were male. The mean age was 43.1 (range, 19-64 years). Transcutaneous tibial nerve stimulation was found to reduce the time patients spent in the toilet. The use of softeners decreased from 76.2% to 20% (P < .001). Obstructive defecation (P < .001), colonic inertia (P < .001), pain (P < .001), and Constipation Severity Instrument total score (P < .001) improved after the 6-week treatment period. The treatment effect persisted until the 12th week. Conclusion: Bilateral transcutaneous tibial nerve stimulation is a noninvasive, easily applicable, and effective treatment for functional constipation, without major adverse effects. Large randomized controlled trials are required so that transcutaneous tibial nerve stimula- tion can be established as an alternative treatment for functional constipation that is resistant to standard care and laxative agents. Cite this article as: Gokce AH, Gokce FS, Iliaz R, Gulaydin N. Transcutaneous tibial nerve stimulation as therapy for functional constipation. Turk J Gastroenterol. 2022;33(7):565-569.